Barong dan Rangda: Memaknai Sebuah Kearifan Lokal dari Budaya Bali - Ramadhani, I Gusti Ngurah Aswin (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2011)
One of the wellkown Balinese sacred art is 'Barong and Rangda' dance, which symbolises the two supernatural and complementary powers, namely the good and the evil, the white and the black, the right and the left. The writer argues that it actually has a very long history, an encounter and acculturation of various traditions, such as of the Javanese Hinduism, the Chinese culture, and the religious tradition and cosmology of the Balinese. If one wants to comprehend the Balinese way of life, he or she should have to understand these two supernatural powers which are basically complementary to each other.